Individualism in Georgian Writing - Kajaia, Manana; Mamardashvili, Nino (European Scientific Journal, ESJ, 2025)
Individualism is a Western phenomenon. Its manifestation is felt in the East from a cultural point of view, despite Eastern collectivism and, when considered from a political perspective, a certain despotism. Individualism manifests in a person’s moral actions within a socio-political environment. In terms of revealing individualism, sixteenth-century Georgian writing is particularly important. If we judge by the historical context, the main lines of Eastern and Western individualism are outlined. The country’s historical context shaped the individualism of Georgian literature - the country and the nation, throughout their history, constantly needed to protect their identity, especially after the 19th century, when the country lost its independence and became part of the Russian Empire for two centuries. The traumatic experience of colonialism was most poignantly reflected in literature. We will discuss this issue based on a contrastive analysis, using historical and comparative research methods. Georgian literature dates back to the 5th century, and its origin is connected with the proclamation of Christianity as the state religion in Georgia. Until the 11th century, Georgian literature was primarily religious. While it had a specific purpose, it nurtured the most important aspect: the individual and their relationship with the outside world. Human nature also reflects divine nature, as human nature is originally embedded in the divine.